Optimization of protein and peptide drugs based on the mechanisms of kidney clearance - Wu, Huizi; Huang, Jiaguo (Protein and peptide letters, 2018)
Background: Development of proteins and peptides into drugs has been considered as a promising strategy to target certain diseases. However, only few proteins and peptides have been approved as new drugs into the market each year. One major problem is that proteins and peptides often exhibit short plasma half-life times, which limits the application for their clinical use. In most cases a short half-life time is not effective to deliver sufficient amount of drugs to the target organs and tissues, which is generally caused by fast renal clearance and low plasma stability due to proteolytic degradation during systemic circulation, because that the most common clearance pathway of small proteins and peptides is through glomerular filtration by the kidneys. Conclusion: In this review, enzymatic degradation of proteins and peptides were discussed. Furthermore, several approaches to lengthen the half-life of peptides and proteins drugs based on the unique structures of glomerular capillary wall and the mechanisms of glomerular filtration were summarized, such as increasing the size and hydrodynamic diameter; increasing the negative charge to delay the filtration; increasing plasma protein binding to decrease plasma clearance.